Phenotype-based discovery of a HeLa-specific cytotoxic molecule that downregulates HPV-mediated signaling pathways via oxidative damage. Issue 31 (25th July 2019) - Lee, Sanghee; Cho, Wansang; Hong, Sungyoul; Yi, Sihyeong; Kim, Heejun; Baek, Soo Yeon; Park, Hankum; Jung, Jinjoo; Shin, Young Kee; Park, Seung Bum
Abstract : Selective bioactive compounds have emerged as major players in chemical biology for their potential in disrupting diverse biological pathways with minimal adverse effects. Abstract : Selective bioactive compounds have emerged as major players in chemical biology for their potential in disrupting diverse biological pathways with minimal adverse effects. Using phenotypic screening, we identified an anti-cancer agent, SB2001, with a highly specific cytotoxicity toward HeLa human cervical cancer cells. The subsequent mechanistic study revealed that SB2001 induced apoptotic cell death through restoring p53 function and suppressed the human papillomavirus (HPV)-mediated oncoprotein signaling pathway via oxidative damage in HeLa cells. SB2001 also selectively induced HeLa-specific tumor regression without any adverse effects in an in vivo tumor xenograft model, demonstrating its potential as a promising chemical probe.